2010
DOI: 10.1155/2010/409640
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Testosterone, Progesterone, Seminal Antisperm Antibody, and Fructose Levels among Jordanian Males with a History of Infertility

Abstract: Due to the biochemical complexity of seminal fluid, we attempt to study the possible correlation between fructose, which is secreted under the effect of androgen hormone, and autoimmunity, which might play a role in varicocele associated infertility, in reducing sperm motility. Seminal fructose, antisperm antibodies (ASAs) and blood steroids hormones (testosterone and progesterone) levels were measured in 66 infertile males with varicocele and 84 without varicocele referred for fertility treatment. Seminal ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 40 publications
2
37
0
Order By: Relevance
“…Seminal fructose correlates positively with spermatozoa DNA fragmentation, 55 and has been found to be both significantly up-and down-regulated in different aetiologies of male infertility. 56,57 In this study, found that seminal fructose level (r=0.47, P<0.05) correlated positively with sperm DNA fragmentation index in group with normozospermia. In group with oligozospermia found negative correlation (r=-0.24, P<0.05) between seminal fructose with sperm DNA fragmentation.…”
Section: Discussionsupporting
confidence: 55%
“…Seminal fructose correlates positively with spermatozoa DNA fragmentation, 55 and has been found to be both significantly up-and down-regulated in different aetiologies of male infertility. 56,57 In this study, found that seminal fructose level (r=0.47, P<0.05) correlated positively with sperm DNA fragmentation index in group with normozospermia. In group with oligozospermia found negative correlation (r=-0.24, P<0.05) between seminal fructose with sperm DNA fragmentation.…”
Section: Discussionsupporting
confidence: 55%
“…Several studies demonstrate that in varicocele, the secretions of impaired sex accessory glands, such as fructose, might have a negative influence on motility of ejaculated spermatozoa (26). Other studies assert that fructose levels in varicocele samples are not significantly different to those of samples without varicocele (27). Steroid hormones, such as testosterone, play a fundamental role not only in sexual differentiation and in expression of secondary sexual characteristics but also, in spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is not observed in varicocele samples (33). Jackaman et al (34) and Al-Daghistani et al (27) demonstrate that testosterone levels in samples without varicocele are lower than in samples with varicocele. This feature may indicate severe atrophy of seminiferous tubules, sclerosis and Leydig cells hyperplasia, causing the humoral immune response and then ASA (Anti Sperm Antibodies) production; these latter, as known, are involved in a reduced sperm motility.…”
mentioning
confidence: 99%
“…In particular, a cut‐off value of 50% of motile spermatozoa with ASA was established as clinically relevant . Using these procedures, a 5–39% incidence of sperm surface autoantibodies has been reported in men suspected of infertility …”
Section: Introductionmentioning
confidence: 99%